PREREQUISITES FOR NATURAL APPROACHES IN LINGUISTICS - Abdullaev Sobir Samadovich (Лучшие интеллектуальные исследования, 2024)
The article analyzes a number of points of ecolinguistics, which are the prerequisites for methodological and conceptual system of household and outside inquire about. Ecolinguistic strategies are highlighted and the issues of ecolinguistics in medialinguistics are sketched out. Specific consideration is paid to the creation of an integrator approach as the premise of orderly biology. The recognizing highlights of environmental worldview appearance within the science of dialect based on the developing slant of ecolinguistics are emphasized. The article bargains with the terms and definitions related with the ecolinguistics , which speak to two fundamental headings: